USAGES AND TRANSLATIONS OF THE ITALIAN TANTO IN SPOKEN LANGUAGE - Patrizia Giampieri (RiCognizioni, 2025)
This paper explores the meanings, usages in context and translations into English of several tanto constructions (e.g., tanto meno, tanto poi, così tanto che, perché tanto, tanto è vero, etc.). The phrasemes are searched for in a spoken Italian corpus, where frequencies, meanings and usages in context are accounted for and discussed. Translation options are then retrieved from Italian-English parallel corpora, where also occurrences and meanings are taken into consideration. Such translations are corroborated or challenged by consulting spoken American and spoken British English corpora. Relative frequencies, pragmatic meanings, and usages are compared across all corpora. The findings reveal that several translations of the tanto constructions are retrieved from the spoken American English corpus; some others are obtained from the British English corpus. Conversely, the parallel corpora sporadically give rise to infrequent or unnatural language samples, especially as far as idiomatic expressions are concerned. Hence, the paper findings bring to the fore different patterns and pragmatic meanings of the source and target expressions. In particular, the tanto expressions, their translations, frequencies, and language patterning may greatly differ in terms of content and context.